Performance of Microbial Fuel Cell for Wastewater Treatment and Electricity Generation - Yavari, Z; Izanloo, H; Naddafi, K; Tashauoei, H.R; Khazaei, M (Center of Biomass & Renewable Energy, Diponegoro University, 2013)
Renewable energy will have an important role as a resource of energy in the future. Microbial fuel cell (MFC) is a promising method to obtain electricity from organic matter and wastewater treatment simultaneously. In a pilot study, use of microbial fuel cell for wastewater treatment and electricity generation investigated. The bacteria of ruminant used as inoculums. Synthetic wastewater used at different organic loading rate. Hydraulic retention time was an effective factor in removal of soluble COD and more than 49% removed. Optimized HRT to achieve the maximum removal efficiency and sustainable operation could be regarded 1.5 and 2.5 hours. Columbic efficiency (CE) affected by organic loading rate (OLR) and by increasing OLR, CE reduced from 71% to 8%. Maximum voltage was 700mV. Since the microbial fuel cell reactor considered as an anaerobic process, it may be an appropriate alternative for wastewater treatment